2020
DOI: 10.29117/cic.2020.0022
|View full text |Cite
|
Sign up to set email alerts
|

BIM Based Facility Condition Assessment

Abstract: Current practices of using traditional methods of managing data using spreadsheets or hard paper copies for various building data, are commonly being used during building inspection and condition assessment. Building Information Modelling (BIM) can immensely help in solving problems of facility inspection by generating and managing digital representation of the physical and functional characteristics of a facility. This paper describes a model, which is developed to integrate the physical and environmental con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For maintenance and rehabilitation plans, it has been suggested that overall costs must be minimized, and the building condition must be greater than a certain minimum accepted level (while maintaining resource and budget constraints). Since maintenance cost is inversely proportional to the building’s condition (Pen et al , 2010; Al-Sakkaf et al , 2020b), facility managers are faced with the task of finding a balance between both factors (Faqih et al , 2020a, b). Another challenge relates to determining the optimal maintenance option for several systems (under resource constraints) over different periods of time.…”
Section: Research Model Developmentmentioning
confidence: 99%
“…For maintenance and rehabilitation plans, it has been suggested that overall costs must be minimized, and the building condition must be greater than a certain minimum accepted level (while maintaining resource and budget constraints). Since maintenance cost is inversely proportional to the building’s condition (Pen et al , 2010; Al-Sakkaf et al , 2020b), facility managers are faced with the task of finding a balance between both factors (Faqih et al , 2020a, b). Another challenge relates to determining the optimal maintenance option for several systems (under resource constraints) over different periods of time.…”
Section: Research Model Developmentmentioning
confidence: 99%
“…It was observed that the framework provided a time-saving opportunity for the analysis of a building's physical and environmental condition. Faqih et al (2020a, b) conducted a review on the different elements that can adversely impact the physico-environmental condition of a building. The findings reported in this study are beneficial to facility managers in order to help them identify, ahead of time, these elements that could cause the building to deteriorate.…”
Section: Introductionmentioning
confidence: 99%